SUPPLY AND PERFORMANCE OF COFFEE MARKETS IN GOLOLCHA DISTRICT OF OROMIA REGION, ETHIOPIA - Degaga, Jima; Alamerie, Kumilachew (Economics of Agriculture, 2020)
The objectives of the study were to identify performance of coffee market and factors affecting market supply of coffee by smallholder farmers. The data was collected through personal interviews from a total of 213 respondents. The result of Focus Group Discussion revealed coffee producers in the study area are exposed to low and volatile price. Based on two stage least squares model, we found that amount of coffee produced, sex of the household heads, educational level, family size, land allocated to coffee production and access to market information had positively and significantly influenced amount of coffee supplied to the market. Therefore, emphasis should be given on controlling illegal traders and enhancing market infrastructure, promotion of cooperatives, increasing level of coffee production and expansion of education facilities in the study area